Towards Establishment of a Computerised Petroleum Data Bank (COPED) of the Oil and Natural Gas Commission of India - Sastri, V. V. (Journal of Information and Knowledge, 1978)
Details regarding Oil and Natural Gas Commission (ONGC) are given. The need for a Computerised Petroleum Data Bank is emphasised. The objectives, functions, and information services to be given by COPED are discussed.